Expression of bone morphogenetic protein receptors in bovine oviductal epithelial cells: Evidence of autocrine BMP signaling - Valdecantos, Pablo Alberto (2017)
Members of the transforming growth factor beta (TGF-β) family, including bone morphogenetic proteins (BMPs), are expressed in the epithelial cells of the mammalian oviduct. These signaling molecules play important roles in development and tissue homeostasis; however, little is known about their function in the mammalian oviduct. In the present study, RT-qPCR was used to analyze the mRNA abundance of BMP type I (BMPR1A, BMPR1B, ACVR1) and type II receptors (BMPR2, ACVR2A, ACVR2B) in the bovine oviduct epithelial cells (BOEC) isolated from ampulla and isthmus at both the follicular (FP) and the luteal (LP) phase of the estrous cycle. Results indicate that mRNAs for all the BMP receptors studied are expressed in the BOEC. Significant mRNA abundance differences were observed for both BMPR1B and ACVR2B when comparing both the ampulla and isthmus regions with the greater abundance at the isthmus. When both FP and LP samples were compared, ACVR2B mRNA showed greater abundance during the LP, with significant differences in the isthmus region. These variations highlight differences between the isthmus and ampulla regions of the oviduct. By means of wound healing assays on BOEC primary cultures, exogenous recombinant human BMP5 induced a significant increase in wound healing at 24 h. The observed changes at the mRNA abundance of components of the signaling pathway and the BMP5 effect on oviductal epithelial cells suggest a possible autocrine role for the BMP pathway that could affect epithelial cell functions necessary for normal physiology and reproductive success in BOEC homeostasis.